2014
DOI: 10.4103/0019-5413.132525
|View full text |Cite
|
Sign up to set email alerts
|

Autograft reconstructions for bone defects in primary total knee replacement in severe varus knees

Abstract: Background:Large posteromedial defects encountered in severe varus knees during primary total knee arthroplasty can be treated by cementoplasty, structural bone grafts or metallic wedges. The option is selected depending upon the size of the defect. We studied the outcome of autograft (structural and impaction bone grafting) reconstruction of medial tibial bone defects encountered during primary total knee replacement in severe varus knees.Materials and Methods:Out of 675 primary varus knees operated, bone def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
1
11
0
4
Order By: Relevance
“…One study evaluating prerequisites for complete graft incorporation in 24 primary or revision knees reported that pertinent coverage of the graft by the component can prevent resorption of unstressed graft which may contribute to failure by collapse [ 1 ]. However, our study included one case of undersized tibial component on the cortical wall of the proximal tibia related to an our unintentional error during the initial learning curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study evaluating prerequisites for complete graft incorporation in 24 primary or revision knees reported that pertinent coverage of the graft by the component can prevent resorption of unstressed graft which may contribute to failure by collapse [ 1 ]. However, our study included one case of undersized tibial component on the cortical wall of the proximal tibia related to an our unintentional error during the initial learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…A severe tibial bone defect in primary total knee arthroplasty (TKA) is one of the biggest challenges to treat for the surgeon, which can lead to a poorly balanced tibial component. Moreover, an uncontained defect is associated with a resultant angular deformity that is usually posterior and medial in a more than 20° varus knee from primary TKA [ 1 ]. The management of bone defects on the tibial aspect can vary depending on the size and location of the loss of bone, and it is necessary to consider other patient specific factors such as age, functional requirements, and bone quality.…”
Section: Introductionmentioning
confidence: 99%
“…It is not preferable that the proximal tibia cut level is lower than accepted measures. [ 1 , 6 , 12 ] That is because the tibial base plate cannot be supported by softer cancellous bone and the tendons and ligaments adhering to the proximal tibia may be damaged [ 1 , 6 ]. For this reason, most of the defects of tibial medial plateau have to be reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…In advanced varus deformed knees, the defect in the proximal medial tibia usually requires additional surgical procedures. [ 1 - 3 ] Methods used by surgeons for the reconstruction of this defect consist of providing support through cement, metal wedges, the use of autograft, etc . [ 1 , 4 - 8 ] Although TKA has been known to be a satisfying surgery with a success rate above %90, in the case of advanced varus knee deformity, the outcomes of TKA is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation